2021
DOI: 10.1007/s10666-021-09756-8
|View full text |Cite
|
Sign up to set email alerts
|

Do Risk Preferences Really Matter? The Case of Pesticide Use in Agriculture

Abstract: Even if there exists an extensive literature on the modeling of farmers' behavior under risk, actual measurements of the quantitative impact of risk aversion on input use are rare. In this article we use simulated data to quantify the impact of risk aversion on the optimal quantity of input and farmers' welfare when production risk depends on how much of the input is used. The assumptions made on the technology and form of farmers' risk preferences were chosen such that they are fairly representative of crop f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Given the high importance of risk in agricultural production, the consideration of cognitive biases with respect to decision‐making under uncertainty may add an important level of detail to the simulation of agricultural systems (Howley et al, 2017). Considering the cumulative prospect theory in simulating farmers’ decision‐making has shown that it can improve the correlation between observed and simulated land‐use data and farmer behaviour (e.g., Appel & Balmann, 2019; Bontemps et al, 2020). The advantage of FARMIND is that it allows both the expected utility theory and prospect theory decision rules to be considered in the same simulation, which provides an important entry point to diversify the representative agent model that assumes only one type of decision process (Harrison & Rutström, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the high importance of risk in agricultural production, the consideration of cognitive biases with respect to decision‐making under uncertainty may add an important level of detail to the simulation of agricultural systems (Howley et al, 2017). Considering the cumulative prospect theory in simulating farmers’ decision‐making has shown that it can improve the correlation between observed and simulated land‐use data and farmer behaviour (e.g., Appel & Balmann, 2019; Bontemps et al, 2020). The advantage of FARMIND is that it allows both the expected utility theory and prospect theory decision rules to be considered in the same simulation, which provides an important entry point to diversify the representative agent model that assumes only one type of decision process (Harrison & Rutström, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FARMIND can be used to test and develop hypotheses about farmers’ behaviour in the context of counterfactual analysis or the implementation of new agri‐environmental policy measures. Moreover, it builds a bridge to recent empirical applications of the cumulative prospect theory in agriculture (e.g., Bontemps et al, 2020; Iyer et al, 2020) and addresses the challenges in understanding decision‐making under uncertainty, which cannot be identified from empirical data (Hellerstein et al, 2013; Just & Just, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk preference refers to attitudes towards risk and is a key factor in determining how people make decisions [ [37] , [38] , [39] ]. Risk-averse individuals tend to be more cautious, and prioritize stability and reliability over potential, but risky gains [ 40 ]. Conversely, individuals or groups tolerant to risk might exhibit a greater propensity to adopt new ideas, technologies, or practices despite the accompanying uncertainties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process of embracing innovations involve a deliberate evaluation of potential risks against potential gains. Diverse risk preferences among entities or individuals often result in varying inclinations toward adopting different practices [ 23 , 32 , 40 , 50 , 51 ]. For instance, when farmers anticipate simultaneous increases in returns and risks, risk-averse households are less inclined to opt for farming strategies that escalate risk despite the higher returns.…”
Section: Literature Reviewmentioning
confidence: 99%